2021
DOI: 10.3390/agronomy11102001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Polyphenolic Profiles and Antibacterial Properties of Leaf Extract of Various Paulownia spp. Clones

Abstract: Paulownia spp. are widely distributed ornamental trees with leaves abundant in secondary metabolites of high medicinal potential. Eighteen breeding clones of Paulownia spp. were tested in terms of their antioxidant activity and total polyphenolic contents. The 50% ethanolic extracts (2 g/30 mL) of leaves and petioles were compared in the screening step. Eight paulownia clones were selected for detailed analyses including HPTLC polyphenolic profile, verbascoside content and antibacterial activity against five b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Paulownia is one of the traditional Chinese medical ( 13 ), which contains a variety of active ingredients such as flavonoids, phenolic acids, saponins, phenylethanoid glycosides, lignans, and triterpenoids in its leaf, fruit, and flower ( 12 , 19 , 35 ), with multiple pharmacological and economical values ( 18 ). Our GC mass analysis demonstrated that the methanolic extract of P. tomentosa included large amounts of thymol, phytol, flavonoids, and other bioactive compounds, which indicates the great efficacy of methanol as an organic solvent in extracting the primary bioactive molecules found within leaves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paulownia is one of the traditional Chinese medical ( 13 ), which contains a variety of active ingredients such as flavonoids, phenolic acids, saponins, phenylethanoid glycosides, lignans, and triterpenoids in its leaf, fruit, and flower ( 12 , 19 , 35 ), with multiple pharmacological and economical values ( 18 ). Our GC mass analysis demonstrated that the methanolic extract of P. tomentosa included large amounts of thymol, phytol, flavonoids, and other bioactive compounds, which indicates the great efficacy of methanol as an organic solvent in extracting the primary bioactive molecules found within leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Our GC mass analysis demonstrated that the methanolic extract of P. tomentosa included large amounts of thymol, phytol, flavonoids, and other bioactive compounds, which indicates the great efficacy of methanol as an organic solvent in extracting the primary bioactive molecules found within leaves. In addition, methanol is highly effective in extracting essential oils from plant material, particularly, the leaves ( 16 , 19 ). Thus, this research studied the incorporation of P. tomentosa leaf extract into broiler diets and has shown that it is a viable strategy for improving performance and general health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is native to southeastern Asia (especially China), where it has been cultivated for decorative, cultural, and medicinal purposes for over 2000 years [ 1 , 2 ]. It is also known as the princess tree, royal tree, Kiri tree, empress tree, and phoenix tree [ 3 , 4 ], while its Chinese name is 泡桐 (pāo tóng) [ 5 ]. The genus Paulownia is believed to comprise 6 to 17 species depending on taxonomic classification [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Paulownia is believed to comprise 6 to 17 species depending on taxonomic classification [ 6 ]. Of these, P. tomentosa , P. elongata , P. fortunei, and P. catalpifolia are considered the most popular [ 4 ].…”
Section: Introductionmentioning
confidence: 99%